Growth Stimulatory Effects and Genome-Wide Transcriptional Changes Produced by Protein Hydrolysates in Maize Seedlings - Santi, Chiara; Zamboni, Anita; Varanini, Zeno; Pandolfini, Tiziana (Frontiers in Plant Science, 2017)
Protein hydrolysates are an emerging class of crop management products utilized for improving nutrient assimilation and mitigating crop stress. They generally consist of a mixture of peptides and free amino acids derived from the hydrolysis of plant or animal sources. The present work was aimed at studying the effects and the action mechanisms of a protein hydrolysate derived from animal residues on maize root growth and physiology in comparison with the effects induced by either free amino acids or inorganic N supply. The application of the protein hydrolysate caused a remarkable enhancement of root growth. In particular, in the protein hydrolysate-treated plants the length and surface area of lateral roots were about 7 and 1.5 times higher than in plants treated with inorganic N or free amino acids, respectively. The root growth promoting effect of the protein hydrolysate was associated with an increased root accumulation of K, Zn, Cu and Mn when compared with inorganic N and amino acids treatments. A microarray analysis allowed to dissect the transcriptional changes induced by the different treatments demonstrating treatment-specific effects principally on cell wall organization, transport processes, stress responses and hormone metabolism.